Frequency and character of low back pain among outpatients in Moscow. Report II - T. V. Dubinina; E A Galushko; S. F. Erdes (Научно-практическая ревматология, 2008)
Material and methods. 1300 pts aged 18 to 50 years actively visited out-patients’ clinic №17 of South Administrative District were examined during a month with a questionnaire developed in the Institute of Rheumatology of RAMS. Results. LBP is a frequent cause of pt visits in outpatient practice. Spine X-ray was the most frequent diagnostic method used in such cases. Spine osteochondrosis was the most frequent diagnosis in these pts. Frequency of “red flags” did not exceed 10%.